PEMBERDAYAAN MASYARAKAT MELALUI MANAJEMEN ZAKAT FITRAH PADA MASA PANDEMI DI DESA MOTOLOHU KECAMATAN HELUMO KABUPATEN BOLAANG MONGONDOW SELATAN - Perdana, Dian Adi (Turast: Jurnal Penelitian dan Pengabdian, 2021)
Zakat is to purify the rights that a person has and separate the rights of others contained therein, so that it can provide benefits to others. The Indonesian government has regulated the management of zakat in UU no. 38 of 1999 about Zakat Management, regulations are made to facilitate the community in the process of collecting, managing and distributing zakat. This research discusses the management of zakat fitrah in Motolohu Village, Bolaang Mongondow Selatan Regency during the pandemic. The condition of the community is disturbed in paying zakat fitrah during the pandemic, especially in the economic sector. Researchers examined the management of zakat fitrah carried out by the government and zakat officials in Motolohu Village during the pandemic, the collection process, distribution and distribution of zakat fitrah during the pandemic, as well as the benefits of zakat fitrah for the community. This study uses a descriptive qualitative approach with various questions to the informants to get answers to social problems about community empowerment through zakat fitrah management in Motolohu Village during the pandemic. Data collection techniques used observation, interviews and documentation to several sources. The data that has been obtained are then analyzed in order to obtain the results presented in the form of conclusions. The results of research on the collection, management and distribution in Motolohu Village were carried out with different techniques. Collection of zakat, zakat administrators visit the houses of people who want to pay zakat. Zakat payments are divided into 3 levels, the process of collecting zakat is carried out optimally by paying attention to people's income. The public is advised to donate Rp. 5,000 / person. Distribution of zakat fitrah, officers distribute zakat fitrah equipped with health protective equipment. The benefits of zakat fitrah that are obtained by muzakki in Motolohu Village are the implementation of amaliyah which can still be applied by giving to those who have the right, especially in a pandemic situation.